Use of Corpus Technologies for the Development of Lexical Skills - MUKHAMADIAROVA, Albina Fanilevna; CASERTA, Lilia Fidarisovna; KULKOVA, Mariya Alexandrovna; REUTER, Kirsten (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The introduction of informational technologies in the modern educational process is an essential part of the successful work of the teacher and the guaranty of the achievement of learning outcomes. The text corpus is one of the modern resource tools for the creation of language learning assignments for students. In addition, we present teaching materials for studying the homonymy and polysemy of the words. We offer two different forms of organization of the learning process with emphasis on corpus technology: teacher presenting select assignments to independently working students with texts from a text corpus, as a mini-research project. RESUMEN La introducción de tecnologías de información en el proceso educativo moderno es una parte esencial del trabajo exitoso del maestro y la garantía del logro de los resultados del aprendizaje. El corpus de texto es una de las herramientas de recursos modernas para la creación de tareas de aprendizaje de idiomas para estudiantes. Además, presentamos materiales didácticos para estudiar la homonimia y la polisemia de las palabras. Ofrecemos dos formas diferentes de organización del proceso de aprendizaje con énfasis en la tecnología de corpus: el maestro presenta tareas selectas a estudiantes que trabajan independientemente con textos de un corpus de texto, como un mini proyecto de investigación.